Pengaruh Model Penemuan Terbimbing terhadap Pemahaman Konsep Matematika Siswa Sekolah Dasar - Wiwid Satriyo Satriyo; Tuhu Setyono (Universitas Negeri Makassar, 2022)
This study aims to describe the effect of the guided discovery model on the understanding of elementary school students' mathematical concepts. The research method used is a quasi-experimental research method. Quasi-experimental design used pre-test post-test. The research population was 74 students. The research sample consisted of 54 students with 27 students in the experimental class and 27 in the control class. The data collection technique used is to measure students' understanding of mathematical concepts. The research instrument used was a student's mathematical concept understanding test sheet. The data analysis technique was carried out using quantitative data analysis techniques. The results showed that the understanding of mathematical concepts of the group of students who used the guided discovery model was higher than the understanding of the mathematical concepts of the control group who used the non-guided discovery model. The guided discovery learning model has a significant effect on the non-guided discovery model in terms of understanding elementary school students' mathematical concepts. The guided discovery model must continue to be applied by the teacher so that the understandings of other students can develop optimally.